Mesoporous sodium four-coordinate aluminosilicate nanoparticles modulate dendritic cell pyroptosis and activate innate and adaptive immunity. Issue 29 (20th July 2022) - Tang, Jie; Yang, Yang; Qu, Jingjing; Ban, Wenhuang; Song, Hao; Gu, Zhengying; Yang, Yannan; Cai, Larry; Theivendran, Shevanuja; Wang, Yue; Zhang, Min; Yu, Chengzhong
Abstract : Na- IV Al-DMSN acts as both antigen carriers and modulators to "hyperactivate" dendritic cells (DCs) via potassium (K + ) efflux dependent pyroptosis, eventually leading to enhanced adaptive and innate immunity. Abstract : Pyroptosis is a programmed cell death widely studied in cancer cells for tumour inhibition, but rarely in dendritic cell (DC) activation for vaccine development. Here, we report the synthesis of sodium stabilized mesoporous aluminosilicate nanoparticles as DC pyroptosis modulators and antigen carriers. By surface modification of sodium-stabilized four-coordinate aluminium species on dendritic mesoporous silica nanoparticles, the resultant Na- IV Al-DMSN significantly activated DC through caspase-1 dependent pyroptosis via pH responsive intracellular ion exchange. The released proinflammatory cellular contents further mediated DC hyperactivation with prolonged cytokine release. In vivo studies showed that Na- IV Al-DMSN induced enhanced cellular immunity mediated by natural killer (NK) cells, cytotoxic T cells, and memory T cells as well as humoral immune response. Our results provide a new principle for the design of next-generation nanoadjuvants for vaccine applications.